Public Debt and Economic Development in Nigeria (2007-2022) - Joy Ochuole (PhD) Odey (International Journal of Economics and Financial Management, 2026)
This study examined the relationship between public debt and economic development in Nigeria from 2007 to 2022. An ex-post facto design was used in the research. From the annual reports of the Central Bank of Nigeria, the Debt management office, and the Nigeria Bureau of Statistics, researchers gathered secondary data that was utilized in the study. The Independent variable, public debt was proxied as external debt and domestic debt, while the dependent variable was proxied as gross domestic product and per capita income from 2007 to 2022. Canonical correlations were used to analyze the data in SPSS version 26. Public debt (external debt and domestic debt) and economic development (gross domestic product and per capita income) have a substantial association. It was recommended among others that the Nigerian Debt Management Office ensure that loans should be directed to investment.